Burst spinal cord stimulation for pain and motor function in Parkinson's disease: A case series. (2020) - Furusawa, Yoshihiko; Matsui, Ayano; Kobayashi-Noami, Kei; Kojima, Yuriko; Tsubouchi, Ayaka; Todoroki, Daisuke; Abe, Kyoko; Ishihara, Tasuku; Nishikawa, Noriko; Sakamoto, Takashi; Takahashi, Yuji
Abstract: Introduction: Spinal cord stimulation (SCS) is an established strategy for pain reduction used in whole world including Japan to treat chronic intractable pain. Pain is a frequent comorbidity of Parkinson's disease (PD), leading to poorer quality of life. SCS has been reported to effectively reduce pain in PD and may also improve motor function, but most studies have employed the modality of tonic stimulation. As such, the effects of SCS using the newly developed paradigm of burst stimulation in PD remain relatively unexplored. Methods: This case series reviewed PD patients who underwent SCS using BurstDR stimulation to treat intractable lower back pain (LBP). Pain and motor outcomes were assessed before and at several timepoints after implantation over a 24-week observation period. Results: Pain indices (visual analogue scale [VAS] and short-form McGill Pain Questionnaire 2 [SF-MPQ-2] scores) improved in nearly all patients. Improvements were especially notable in the dimension of affective pain (SF-MPQ-2). Functional motor improvements were evident in the Unified Parkinson's Disease Rating Scale (UPDRS), especially walking-related items, and timed-up-and-go (TUG) test performance, which generally persisted through week 24 of observation. Conclusion: Burst SCS improved pain (especially the affective component) in PD patients with LBP, with effects generally lasting for at least 24 weeks. Neither paresthesia nor obvious adverse events were experienced in any case. Motor symptoms as scored of UPDRS Part III had the trends of improvement in lower limb akinesia at week 24 and gait at week 4. These findings suggest that burst SCS may be an effective treatment option for LBP and may be influenced to gait-related motor symptoms in PD. Highlights: Burst spinal cord stimulation (SCS) is used for chronic refractory pain in Parkinson's disease (PD). We discussed in this paper about five PD patients receiving burst SCS for lower back pain. Burst SCS improved affective pain in PD and shortened TUG score. These effects persisted for at least 24 weeks. Burst SCS may be an effective treatment option for pain and motor disturbance in PD.